Aspek Sintagmatis dan Kolokasi dalam Sinonimi Taksempurna Bahasa Prancis - Sutanto, Irzanti (UI Scholars Hub, 2003)
Synonymous verbs are often confusing because on the one hand verbal pairs have the same meanings but on the other they cannot replace one another in all contexts. This paper examines the contexts of synonymous verbal pairs in French. It shows that aspects that limit the synonymity of a set of words are verbal meanings, semantic characteristics of accompanying words, verbal valence, syntactyc structure, and the commoness of usage of the words. The observation shows that 1) the contexts of the synonymous pairs cannot replace one another although the meanings of both are the same, and 2) the difference in meanings is due to the fact that each word is polysemic.